2013
DOI: 10.1021/es4025723
|View full text |Cite
|
Sign up to set email alerts
|

From Missing Source to Missing Sink: Long-Term Changes in the Nitrogen Budget of a Northern Hardwood Forest

Abstract: Biogeochemical monitoring for 45 years at the Hubbard Brook Experimental Forest in New Hampshire has revealed multiple surprises, seeming contradictions, and unresolved questions in the long-term record of ecosystem nitrogen dynamics. From 1965 to 1977, more N was accumulating in living biomass than was deposited from the atmosphere; the “missing” N source was attributed to biological fixation. Since 1992, biomass accumulation has been negligible or even negative, and streamwater export of dissolved inorganic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 64 publications
2
61
0
Order By: Relevance
“…In closed-canopy forest stands, the pools of primary importance are live and dead woody biomass, as well as soil carbon. Here we focus on changes in woody carbon stocks and assume that changes in soil carbon stocks were minimal as was found from measurements at mature stands in nearby Hubbard Brook Experimental Forest (Yanai et al, 2013). Changes in soil carbon stocks would be very difficult to detect over a 13 year study period (Vadeboncoeur et al, 2012).…”
Section: Changes In Carbon Stocks (δC)mentioning
confidence: 99%
“…In closed-canopy forest stands, the pools of primary importance are live and dead woody biomass, as well as soil carbon. Here we focus on changes in woody carbon stocks and assume that changes in soil carbon stocks were minimal as was found from measurements at mature stands in nearby Hubbard Brook Experimental Forest (Yanai et al, 2013). Changes in soil carbon stocks would be very difficult to detect over a 13 year study period (Vadeboncoeur et al, 2012).…”
Section: Changes In Carbon Stocks (δC)mentioning
confidence: 99%
“…Such results often lead to fertilizer overapplication in agricultural systems (Liu et al 2010) and then to N losses from leaching and denitrification. While gross rates of mineralization are higher and may better correlate with plant N uptake (Osterholz et al 2016), they are rarely measured at the temporal and spatial scales that are needed to resolve the complex processes that regulate bioavailable N. In addition, many natural ecosystems exhibit a ''missing sink'' phenomenon wherein soils store more N than can be accounted for by N budgeting (Bernal et al 2012;Yanai et al 2013;van Groenigen et al 2015). This suggests there are other pathways of N storage and production that are not adequately represented by standard laboratory measures of N availability.…”
Section: Introductionmentioning
confidence: 99%
“…() reported that 0–70% of atmospheric N was retrieved in runoff from forest catchments in Europe and North America. In other investigations, part of the atmospheric N was accumulated in trees, denitrified, or lost through runoff (Nadelhoffer et al ., ; Yanai et al ., ), or stayed in the soil (e.g. 70% reported by Nadelhoffer et al ., ).…”
Section: Resultsmentioning
confidence: 97%